Case Report: Acute Fulminant Myocarditis and Cardiogenic Shock After Messenger RNA Coronavirus Disease 2019 Vaccination Requiring Extracorporeal Cardiopulmonary Resuscitation - Lim, Yongwhan; Kim, Min Chul; Kim, Kye Hun; Jeong, In-Seok; Cho, Yong Soo; Choi, Yoo Duk; Lee, Jong Eun (Frontiers in Cardiovascular Medicine, 2021)
Recently, myocarditis following messenger RNA (mRNA) coronavirus disease 2019 (COVID-19) vaccination has become an important social issue worldwide. According to the reports so far, myocarditis related to mRNA COVID-19 vaccination is rare and usually associated with a benign clinical course without intensive care or any sequelae of fulminant myocarditis. Here, we report a case of acute fulminant myocarditis and cardiogenic shock after the mRNA COVID-19 vaccination, requiring extracorporeal cardiopulmonary resuscitation. Clinicians should keep in mind the possibility of progression to fulminant myocarditis in patients who presented with suggestive symptoms or signs of myocarditis after the COVID-19 vaccination.